PENGARUH NILAI TUKAR MATA UANG RUPIAH DENGAN US DOLLAR TERHADAP HARGA SAHAM DI BEI SETELAH INITIAL PUBLIC OFFERING (IPO) - Nurul Hidayat; Moh. Amin; Junaidi Junaidi (e_Jurnal Ilmiah Riset Akuntansi, 2019)
ABSTRACTThis research was conducted to analyze the effect of Rupiah currency exchange rates on US dollars against stock prices on the IDX after an initial public offering (IPO) ". The sample in this study is a company that conducts an Initial Public Offering (IPO) in 2016-2018. The analytical method used is Simple Linear Regression with SPSS 16, 2019 Software. Based on the results of simultaneous hypothesis testing shows that simultaneously the model formed to predict the exchange rate affects the stock price. Partially, it shows that individual exchange rates have a significant influence on stock prices.Keywords: Currency Exchange Rates and Stock Prices After IPO